Путешествие из Петербурга в Москву - Радищев Александр Николаевич (Книжный магазин Д. И. Ефимова, 1906)
Экземпляры: РК (20231116) / Инвентарный номер: 1127304 / Сис.шифр: 84(2) / Авт.знак: Р 15 / ГРНТИ: 17 / ББК: 84(2=411.2)-4